Recruitment and Data Collection in the 21st Century - Emily J. Cashwell (Grounded Theory Review: An International Journal)
For many people, many aspects of daily life now occur online. Most individuals are well-versed in communication via email and social media, and many are experienced with audio and video conferencing software as a means to hold business meetings and to connect with family and friends. In addition, the coronavirus pandemic has shifted many aspects of modern life, and some universities have imposed research restrictions that prohibit face-to-face interviews. Because of these changes in the structure of modern social and professional life, researchers are faced with new opportunities and challenges in recruiting research participants and collecting data for their studies. Grounded theorists, in particular, are faced with challenges implementing the research design as it was originally developed within the context of these modern circumstances. This article explores social media and audio and video conferencing software as tools that a grounded theorist might consider for virtual participant recruitment and interviewing.